Предмет: Алгебра,
автор: meow769
Помогите,пожалуйста))
Приложения:
Ответы
Автор ответа:
1
cos(π+β)*sin(3π/2+β) - ctg(β-π)*ctg(3π/2 - β) =
-cosβ*(-cosβ) - ctgβ*tgβ = cos²β - 1 = - sin²β
sin(3π/2-α)*cos(π-α) + sin(3π-α)*cos(π/2 - α) + tg(π-α)*tg(3π/2+α)=
= -cosα*(-cosα) + sinα*sinα+(-tgα)*(-ctgα) = cos²α+sin²α+1=1+1=2
sin240 * cos(-330) * tg(-315) ctg240 =-√3/2*√3/2*1*1/√3 = -√3/4
-cosβ*(-cosβ) - ctgβ*tgβ = cos²β - 1 = - sin²β
sin(3π/2-α)*cos(π-α) + sin(3π-α)*cos(π/2 - α) + tg(π-α)*tg(3π/2+α)=
= -cosα*(-cosα) + sinα*sinα+(-tgα)*(-ctgα) = cos²α+sin²α+1=1+1=2
sin240 * cos(-330) * tg(-315) ctg240 =-√3/2*√3/2*1*1/√3 = -√3/4
Похожие вопросы
Предмет: Русский язык,
автор: ZiGZaG4242
Предмет: Русский язык,
автор: Romatskaya05
Предмет: Русский язык,
автор: ДАРЬЯБАД
Предмет: Английский язык,
автор: plzhelpmehelp
Предмет: Русский язык,
автор: egorD117